Placebo-induced somatic sensations: a multi-modal study of three different placebo interventions. - Florian Beissner; Franziska Brünner; Maria Fink; Karin Meissner; Ted J Kaptchuk; Vitaly Napadow (PLoS ONE, 2015)
Somatic sensations induced by placebos are a frequent phenomenon whose etiology and clinical relevance remains unknown. In this study, we have evaluated the quantitative, qualitative, spatial, and temporal characteristics of placebo-induced somatic sensations in response to three different placebo interventions: (1) placebo irritant solution, (2) placebo laser stimulation, and (3) imagined laser stimulation. The quality and intensity of evoked sensations were assessed using the McGill pain questionnaire and visual analogue scales (VAS), while subjects' sensation drawings processed by a geographic information system (GIS) were used to measure their spatial characteristics. We found that all three interventions are capable of producing robust sensations most frequently described as "tingling" and "warm" that can reach consider-able spatial extent (≤ 205 mm²) and intensity (≤ 80/100 VAS). Sensations from placebo stimulation were often referred to areas remote from the stimulation site and exhibit considerable similarity with referred pain. Interestingly, there was considerable similarity of qualitative features as well as spatial patterns across subjects and placebos. However, placebo laser stimulation elicited significantly stronger and more widespread sensations than placebo irritant solution. Finally, novelty seeking, a character trait assessed by the Temperament and Character Inventory and associated with basal dopaminergic activity, was less pronounced in subjects susceptible to report placebo-induced sensations. Our study has shown that placebo-induced sensations are frequent and can reach considerable intensity and extent. As multiple somatosensory subsystems are involved despite the lack of peripheral stimulus, we propose a central etiology for this phenomenon.